Academic Dishonesty in College Students: Do Religiosity and Self-Control Matter? - Uula, Alfi Hanifatul; Sulikah, Sulikah (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
Academic dishonesty among students in numerous nations is on the rise, and if allowed unchecked, it may be hazardous to a person's personality development and even entry into the workforce. The purpose of this study is to investigate the impact of religiousity and self-control on academic dishonesty in Accounting Education students at the State University of Malang. The purposive sampling strategy yielded a total of 96 samples. The data was gathered using an online questionnaire and analyzed using multiple linear regression in a data processing tool (SPSS). According to the findings of the study, religiousity and self-control had a detrimental impact on student academic dishonesty. This suggests that the higher a student's level of religiousity and self-control, the less academic dishonesty he or she commits, and vice versa.